Pelaksanaan Pendidikan dan Pelatihan Teknis untuk Meningkatkan Profesionalisme Pegawai (Studi pada Badan Kepegawaian Daerah Kabupaten Nganjuk) - Yasmita, Winda (Jurnal Administrasi Publik, 2013)
Abstract: Implementation of Technical Education and Training to Improve Employee Professionalism (Study From Employment Agency of Nganjuk Area) : Regional development is planned and thorough expected to create justice , prosperity , and welfare for the masyarakat.Hal can be achieved when local development area supported by professional personnel . Local government efforts in improving the professionalism of employees holding one of them with the implementation of technical training . One of the highlights for the study is the implementation of education and technical training to improve the professionalism of employees Nganjuk BKD , BKD obstacles encountered in the implementation of technical training . The purpose of this study is to analyze and describe the implementation of education and technical training to improve the professionalism of employees BKD Nganjuk BKD and the obstacles encountered in the implementation of technical training . This research uses descriptive qualitative method . The focus in this study ( 1 ) Implementation of the Education and Technical Training to boost the professionalism of employees BKD Nganjuk , and ( 2 ) constraints encountered in the implementation of technical training BKD . The results of the study showed that the persistence of the obstacles encountered in the implementation of BKD Nganjuk education and technical pealtihan to improve the professionalism of employees . Although the implementation of education and technical training to improve the professionalism of employees BKD Nganjuk is going according to the stages of education and training . Keyword: implementation of education and technical training, professionalism of employees, Regional Employment Agency Abstrak: Pelaksanaan Pendidikan dan Pelatihan Teknis untuk Meningkatkan Profesionalisme Pegawai (Studi Pada Badan Kepegawaian Daerah Kabupaten Nganjuk): Pembangunan daerah yang terencana dan menyeluruh diharapkan dapat menciptakan keadilan, kemakmuran, dan kesejahteraan bagi masyarakat.Hal ini dapat dicapai apabila pembangunan daerah didukung oleh aparatur daerah yang profesional. Upaya pemerintah daerah dalam meningkatkan profesionalisme pegawai salah satunya dengan mengadakan pelaksanaan diklat teknis. Salah satu yang menarik untuk diteliti adalah pelaksanaan pendidikan dan pelatihan teknis untuk meningkatkan profesionalisme pegawai BKD Kabupaten Nganjuk, kendala yang dihadapi BKD dalam pelaksanaan diklat teknis. Tujuan penelitian ini adalah untuk menganalisis dan mendeskripsikan pelaksanaan pendidikan dan pelatihan teknis untuk meningkatkan profesionalisme pegawai BKD Kabupaten Nganjuk dan kendala yang dihadapi BKD dalam pelaksanaan diklat teknis. Penelitian ini menggunakan metode kualitatif dengan jenis deskriptif. Fokus dalam penelitian ini (1) Pelaksanaan Pendidikan dan Pelatihan Teknis untuk menigkatkan profesionalisme pegawai BKD Kabupaten Nganjuk, dan (2) Kendala yang dihadapi BKD dalam pelaksanaan diklat teknis. Hasil dari penelitian menunjukkan bahwa masih adanya kendala yang dihadapi BKD Kabupaten Nganjuk dalam pelaksanaan pendidikan dan pealtihan teknis untuk meningkatkan profesionalisme pegawai. Meskipun pelaksanaan pendidikan dan pelatihan teknis untuk meningkatkan profesionalisme pegawai BKD Kabupaten Nganjuk sudah berjalan sesuai dengan tahapan-tahapan penyelenggaraan diklat. Â Kata kunci: pelaksanaan pendidikan dan pelatihan teknis, profesionalisme pegawai, Badan Kepegawaian Daerah